Pathways Utilized For Antenatal Health Seeking Among Women In The Ga East District, Ghana - Aryeetey, R.N.O.; Aikins, M.; Dako-Gyeke, P.; Adongo, P.B. (Ghana Medical Journal, 2015)
Background: Ghana’s maternal mortality ratio has been declining over the last two decades but at a rather slow pace. Poor access to effective maternity care is identified as one of the key challenges of maternity care. The current study mapped out the pathways to pregnancy care seeking among urban-dwelling adult women in a peri-urban district located in the Greater Accra region of Ghana. Methods: A total of 300 women who had a live birth in the last 12 months participated in a community-based survey. They answered questions on care-seeking behavior related to their last pregnancy. A multivariate A logistic regression model was used to identify factors associated with multiple care-seeking behavior. Results: Almost all women in the survey (98%) reported accessing skilled antenatal care (ANC) from a bio-medical provider, although 35% began ANC later than the first trimester. About 45% of women simultaneously utilized both ANC and alternative care providers (ACP) including traditional birth attendants, herbalists, and spiritualists. A complex pathway to antenatal care seeking behavior involving shuttling between providers was observed. Controlling for household wealth, household size, and age, seeking care from multiple providers concurrently were associated with residence in Kwabenya sub-district OR=2.13 (95% CI: 1.28, 3.55) and previous abortion OR=2.08 (95% CI: 1.11, 3.91) Conclusions: Urban-dwelling women in Ga East Dis trict seek antenatal care concurrently from multiple sources. Health system interventions must seek ways to integrate alternative care providers into the existing biomedical health care system.
Research Article
Keywords: multiple care seeking; pathway; alternative care; antenatal